Education for Sustainability through Internationalisation Transnational Knowledge Exchange and Global Citizenship - Handa, Neera (Palgrave Studies in Global Citizenship Education and Democracy, 2018)
This book suggests how the internationalisation of teaching and learning for sustainability can be a vehicle for a two-way flow of knowledge across national, cultural and theoretical boundaries. Establishing links between the internationalisation of education and the ideal of global sustainability, the author presents innovative alternative solutions to address the pressing social, environmental and ethical problems of our age, a global priority demanding an educational response. By engaging with the Hindi concept of tri-vid, the three-in-one unification of knowledge, the author reassesses the very nature of knowledge through the intellectual agency of both students and educators. Once opportunities for alternatives not available in dominant Western knowledge traditions are recognised, the development of an innovative alternative perspective becomes possible. This pioneering book will be of interest to students and scholars of international education, sustainability education and globalisation. Neera Handa is an Adjunct Fellow for Learning Transformations at Western Sydney University, Australia.